2018
DOI: 10.3390/molecules23010168
|View full text |Cite
|
Sign up to set email alerts
|

Structure Characterization of Honey-Processed Astragalus Polysaccharides and Its Anti-Inflammatory Activity In Vitro

Abstract: Honey-processed Astragalus is a dosage form of Radix Astragalus mixed with honey by a traditional Chinese medicine processing method which strengthens the tonic effect. Astragalus polysaccharide (APS), perform its immunomodulatory effects by relying on the tonic effect of Radix Astragalus, therefore, the improved pharmacological activity of honey-processed Astragalus polysaccharide (HAPS) might be due to structural changes during processing. The molecular weights of HAPS and APS were 1,695,788 Da, 2,047,756 Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…A decrease in the molecular weight of honey-processed Astragalus polysaccharide (dextran) was accompanied by its reduced anti-inflammatory activity [9]. A similar trend was observed on investigating a polysaccharide obtained from Schizophyllum commune [10].…”
Section: Introductionsupporting
confidence: 57%
“…A decrease in the molecular weight of honey-processed Astragalus polysaccharide (dextran) was accompanied by its reduced anti-inflammatory activity [9]. A similar trend was observed on investigating a polysaccharide obtained from Schizophyllum commune [10].…”
Section: Introductionsupporting
confidence: 57%
“…The peak at 2927 cm −1 was assigned to C–H asymmetric stretching vibration [28]. In addition, the peak at 1613 cm −1 was the C=O asymmetric stretching of –COO, which further confirmed that uronic acids existed in CVLPs [29,30]. The band at 1420 cm −1 was attributed to the bending vibration of C–H or O–H [31,32].…”
Section: Resultsmentioning
confidence: 97%
“…Compared with APS and CTS, the spectra of the APS/CTS microspheres showed a slight shift at 3,454 and 1,075 cm −1 . The change in the curve of the APS/CTS microspheres indicated that APS could react with CTS (Jiang et al, 2013;Liu et al, 2017;Liao et al, 2018). The DSC thermograms of APS, CTS, and APS/CTS microspheres were shown in Figure 2B.…”
Section: Results Of Ftir and Dscmentioning
confidence: 99%